2001
DOI: 10.1259/bjr.74.888.741103
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic contrast media induced nephropathy: experimental observations and the protective effect of calcium channel blockers

et al.

Abstract: Combined acute inhibition of the synthesis of nitric oxide with L-nitroarginine methyl ester (L-NAME) and of prostacycline synthesis with indomethacin predisposes rats to severe renal injury from radiographic contrast media. The reliability of this pharmacological manipulation in the study of radiographic contrast medium induced nephropathy (RCMN) was investigated. Adult male Sprague-Dawley rats were injected with iv L-NAME (10 mg kg(-1)) and iv indomethacin (10 mg kg(-1)) 15 min apart and prior to injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…A large number of drugs have been used to protect renal function after PCI, such as aminophylline (Shammas et al 2001;Rohani 2010), theophylline (Wang et al 2001), atrial natriuretic peptide (Chen 2009;Morikawa et al 2009), B-type natriuretic peptide (Zhang et al 2010), mannitol (Kelly et al 2008), prostaglandins (McCullough andTumlin 2009), N-acetylcysteine (Thiele et al 2010), sodium bicarbonate (Masuda 2008) and statins (Xinwei et al 2009); however, few of them (Kowalczyk et al 2007;Zoungas et al 2009) have shown exact protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of drugs have been used to protect renal function after PCI, such as aminophylline (Shammas et al 2001;Rohani 2010), theophylline (Wang et al 2001), atrial natriuretic peptide (Chen 2009;Morikawa et al 2009), B-type natriuretic peptide (Zhang et al 2010), mannitol (Kelly et al 2008), prostaglandins (McCullough andTumlin 2009), N-acetylcysteine (Thiele et al 2010), sodium bicarbonate (Masuda 2008) and statins (Xinwei et al 2009); however, few of them (Kowalczyk et al 2007;Zoungas et al 2009) have shown exact protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Combined acute inhibition of the synthesis of NO with L-nitroarginine methyl ester (L-NAME) and of prostacyclin synthesis with indomethacin predisposes rats to severe renal injury from radiographic contrast media (23). The marked impairment of relaxation of renal vessels contracted with norepinephrine observed in the present study suggests a pivotal role of the cyclic AMP system in addition to the cyclic GMP-mediated signaling mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…Although the physiological and pathophysiological mechanisms of Ca 2+ overload in ischemic kidney and RCN have not been fully elucidated, there is evidence indicating that increased cytosolic Ca 2+ may be an important mediator of epithelial cell apoptosis and necrosis [21]. In addition, Ca 2+ channel blockers have been reported to have a protective effect against RCN and ischemic ARF [22,23]. In the present study, ioversol exposure induced a significant increase in [Ca 2+ ] i in NRK-52E cells.…”
Section: Discussionmentioning
confidence: 99%